Leadership development in Higher Education: A literature review and implications for programme redesign. (6th December 2018) - Dopson, Sue; Ferlie, Ewan; McGivern, Gerry; Fischer, Michael D.; Mitra, Mahima; Ledger, Jean; Behrens, Sonja
Abstract: Leadership development (LD) activity and its effectiveness has not been explored rigorously across changing university settings globally. As Higher Education settings change radically throughout the world, Higher Education professionals are operating in more uncertain environments, and leaders are taking increasingly complex and diverse approaches to their leadership roles. LD activities therefore become important in supporting this highly complex context, yet little is known in the literature about LD and its impact in Higher Education. We examine peer‐reviewed work on LD in Higher Education settings globally to understand what may be learned about its content, processes, outcomes and impact. Our results suggest the current literature is small‐scale, fragmented and often theoretically weak, with many different and coexisting models, approaches and methods, and little consensus on what may be suitable and effective in the Higher Education context. We reflect on this state of play and develop a novel theoretical approach for designing LD activity in Higher Education institutions.